2014
DOI: 10.1136/bmjopen-2013-004551
|View full text |Cite
|
Sign up to set email alerts
|

Rates of obstetric intervention and associated perinatal mortality and morbidity among low-risk women giving birth in private and public hospitals in NSW (2000–2008): a linked data population-based cohort study

Abstract: ObjectivesTo examine the rates of obstetric intervention and associated perinatal mortality and morbidity in the first 28 days among low-risk women giving birth in private and public hospitals in NSW (2000–2008).DesignLinked data population-based retrospective cohort study involving five data sets.SettingNew South Wales, Australia.Participants691 738 women giving birth to a singleton baby during the period 2000–2008.Main outcome measuresRates of neonatal resuscitation, perinatal mortality, neonatal admission f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
35
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 44 publications
(52 reference statements)
7
35
0
Order By: Relevance
“…As in our study, Robson et al in Australia (2009, n = 789 240) and Coory et al in Queensland (2009, n = 124 300) reported higher rates of perinatal mortality among public compared with private births at term, despite adjusting for eight and 23 potential confounding factors, respectively (Robson et al, aOR 2.02, 95% CI 1.78–2.29; Coory et al, aOR 2.1, 95% CI 1.5–2.9). Dahlen et al (2014) compared perinatal mortality of term babies born to 237 304 low‐risk women, and found no significant intersector difference after adjusting for maternal and gestational ages (aOR 1.49, 95% CI 0.93–2.41).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…As in our study, Robson et al in Australia (2009, n = 789 240) and Coory et al in Queensland (2009, n = 124 300) reported higher rates of perinatal mortality among public compared with private births at term, despite adjusting for eight and 23 potential confounding factors, respectively (Robson et al, aOR 2.02, 95% CI 1.78–2.29; Coory et al, aOR 2.1, 95% CI 1.5–2.9). Dahlen et al (2014) compared perinatal mortality of term babies born to 237 304 low‐risk women, and found no significant intersector difference after adjusting for maternal and gestational ages (aOR 1.49, 95% CI 0.93–2.41).…”
Section: Discussionmentioning
confidence: 99%
“…We adjusted for major congenital anomalies as part of the treatment effect because the incidence of these may be influenced by the model of care . Adjustments were made for birth method and gestational age because prior research has identified intersector differences in clinical practices with respect to these factors …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Once again the high rate of GDM was seen amongst women born in China and a high caesarean section rate was seen for women born in India. Indian women also had a much higher rate of private health insurance and previous work we have undertaken has demonstrated this and the link between this and high obstetric intervention rates [16,17].…”
Section: Discussionmentioning
confidence: 99%